"It's all about sharing": Can circular initiatives be autonomous food spaces? - deborah lambert (Journal of Political Ecology)
In this article I place into dialogue the challenges of the circular economy (CE) with political ecology by using the notion of autonomy. I examine two circular food initiatives in the capital city region of Brussels, Belgium, a cooperative supermarket and a surplus food redistribution project, with a framework of autonomous food spaces. Inspired by post-capitalist debates on the economy I argue that these spaces are cases of the diverse economy mobilizing autonomous practices and imaginaries. My analysis shows the heterogeneity and complexity of these spaces. It illustrates how urban circular food projects offer examples of possible economic activities that rely on cooperation, solidarity and conviviality instead of profit. It explores the diversity of practices and imaginaries that prefigure a viable and alternative future, and sheds light on our understanding of diverse and circular economies by focusing on the social and political dimensions of CE.